Optimization of BS4 Enzyme production with Different Substrate Thickness and Type of Trays - Tuti Haryati; Arnold P Sinurat; H Hamid; Tresnawati Purwadaria (Jurnal Ilmu Ternak dan Veteriner, 2019)
BS4 enzyme that is produced from solid substrate fermentation (SSF) on coconut cake with Eupenicillium javanicum BS4 in tray bioreactor has been applied as a feed additive. It increases the nutritional value of animal feedstuff. The BS4 production on SSF may be influenced by the better aeration through the perforated trays or by the thinner substrate. The aim of this research is to optimize the production of BS4 with different substrate thicknesses and types of trays. The trial was carried out using a factorial randomized design (2x2x3) with 6 replicates. The first factor was the type of trays: i.e., non-perforated and perforated tray. The second factor was the thickness of the substrate: i.e., 1.5 and 3.0 cm, while the third factor was the duration of fermentation: i.e. 5, and 7 days. The variables observed were moisture content, dry matter loss (DML), mannanase and saccharification activities, soluble protein content, their specific activities, and yield. Statistical analysis showed no interactions between the three factors, but there were interactions between types of trays and substrate thicknesses, as well as type of trays and incubation times on the mannanase activity and yield of mannanase. The results showed that DML was observed on day 7 were around 31.43- 36.89. The highest mannanase activity was observed on the non-perforated tray with 3 cm thickness on day 7. The saccharification activity towards palm kernel meal was better in the non-perforated tray on day 7 but not influenced by The yield value of mannanase and saccharification activities on a non-perforated tray with 3.0 cm thickness on day 7 was also the highest. Based on energy efficiency and the cost of production, it can be concluded that the optimum condition to produce the BS4 enzyme was observed in the non-perforated tray with 3 cm thickness and fermented for 7 days.